Potential role for histone deacetylation in chronic diazepam‐induced downregulation of α1‐GABAA receptor subunit expression. Issue 4 (26th June 2018) - Auta, James; Gatta, Eleonora; Davis, John M.; Pandey, Subhash C.; Guidotti, Alessandro
Abstract: Corroborating evidence indicate that the downregulation of GABAA receptor subunit expression may underlie tolerance to the anticonvulsant and anxiolytic actions of benzodiazepine (BZ) ligands that act as full allosteric modulators (FAMs) of GABA actions at a variety of GABAA receptor subtypes. We and others have shown that 10‐14 days treatment with increasing doses of diazepam (a FAM) resulted in anticonvulsant tolerance and decreased the expression of the α1 GABAA receptor subunit mRNA and protein in frontal cortex. In addition, we have also shown that long‐term treatment with imidazenil, a partial allosteric modulator of GABA action at selective GABAA receptor subtypes, fail to change the expression of the α1 subunit mRNA or induce tolerance to its anticonvulsant or anxiolytic action. However, little is known regarding the potential role of epigenetic mechanisms on long‐term BZ‐induced downregulation of GABAA receptor subunit. Therefore, we examined the role of histone acetylation and DNA methylation mechanisms on long‐term diazepam‐induced downregulation of the α1 subunit mRNA expression in rat frontal cortex. We found that 10 days treatment with increasing doses of diazepam but not imidazenil decreased the expression of the α1 GABAA receptor subunit mRNA and promoter acetylation in frontal cortex. In addition, we also found that 10 days treatment with diazepam but not imidazenil increased the expression of histone deacetylase (HDAC) 1 and 2 in frontal cortex. Thus, the increased expression of HDAC1 and HDAC2 (class 1 HDACs) and consequently increased histone deacetylation mechanism of this class 1 HDACs, may underlie long‐term diazepam‐induced decreased expression of the α1 GABAA receptor subunit mRNA in frontal cortex.